Empagliflozin modulates seizure activity and oxidative stress in rats with epilepsy - Holla, Neha; Adiga, Shalini; Kumari, Meena; Rao Kapettu Gadahad, Mohandas; Naik, Prameetha (Journal of Cellular Neuroscience and Oxidative Stress, 2024)
Drug-resistant epilepsy, a commonly devastating condition, affects more than 50 million people globally. Type 2 diabetes mellitus (T2DM) is associated with an increased risk of neurological disorders, and a potential association between epilepsy and subsequent T2DM has emerged. Inhibiting sodium-glucose linked transporters (SGLTs), which are differentially expressed in the brain, has been shown to reduce epileptic episode activity. This study aimed to evaluate the anticonvulsive effect of empagliflozin in rats with seizures induced by maximal electric shock (MES) and pentylenetetrazol (PTZ). Generalized tonic‒clonic seizures were induced in the rats using an electroconvulsive meter, and pentylenetetrazol was injected to induce absence seizures. The duration of all the stages of seizure and Racine stage scoring (RSS) were performed. Malondialdehyde (MDA), nitric oxide (NO) and reduced glutathione (GSH) levels in the brain tissues were determined. Histopathological analysis of the brain tissues was carried out. A significant (p <0.01) decrease in the duration of tonic hind limb extension (THLE), a significant decrease in the levels of pro-oxidants such as MDA and NO, and an increase in the levels of antioxidants such as GSH were observed in the low dose 10 mg/kg and high dose 20 mg/kg empagliflozin groups compared to the disease control group. Histopathological analysis revealed a greater number of healthy neurons with few dark-stained cells in the treatment groups, suggesting the neuroprotective effect of empagliflozin. The present study showed that empagliflozin modulates epileptic activity. Empagliflozin has a potential role in the management of epilepsy in diabetic patients.
Keywords: Sinirbilim (Diğer); Pharmacology and Pharmaceutical Sciences (Other); Eczacılık ve İlaç Bilimleri (Diğer); Neurosciences (Other); Antioxidants; Maximal electroshock; Pentylenetetrazol; SGLT2 inhibitor; Epilepsy